2014
DOI: 10.1103/physreve.90.042711
|View full text |Cite
|
Sign up to set email alerts
|

Effect of radio frequency fields on the radical pair magnetoreception model

Abstract: Although the radical pair (RP) model is widely accepted for birds' orientation, the physical mechanism of it is still not fully understood. In this paper we consider the RP model in the total angular-momentum representation and clearly show a detailed mechanism for orientation. When only the vertical hyperfine (HF) coupling component is considered, analytical expressions of singlet yield angular profiles are obtained with and without considering the radio frequency field, and when the horizontal HF coupling co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(46 citation statements)
references
References 28 publications
6
40
0
Order By: Relevance
“…As such motions are determined by the interactions of the radicals with the protein environment, this is another property that could have been optimized by evolution. Spin relaxation much slower that 1 μs has been invoked before to explain the apparent sensitivity of birds to weak (nanotesla) monochromatic radiofrequency fields (21,26,53,54). The problem with this proposal is that if there is no possibility of a spike, a coherence time of 1-2 μs is sufficient to achieve the optimum compass performance so that there would be no evolutionary pressure to prolong relaxation times beyond this point (55,56).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…As such motions are determined by the interactions of the radicals with the protein environment, this is another property that could have been optimized by evolution. Spin relaxation much slower that 1 μs has been invoked before to explain the apparent sensitivity of birds to weak (nanotesla) monochromatic radiofrequency fields (21,26,53,54). The problem with this proposal is that if there is no possibility of a spike, a coherence time of 1-2 μs is sufficient to achieve the optimum compass performance so that there would be no evolutionary pressure to prolong relaxation times beyond this point (55,56).…”
Section: Discussionmentioning
confidence: 92%
“…In support of this proposal, the photochemistry of isolated cryptochromes in vitro has been found to respond to applied magnetic fields in a manner that is quantitatively consistent with the radical pair mechanism (15). Aspects of the radical pair hypothesis have also been explored in a number of theoretical studies, the majority of which have concentrated on the magnitude of the anisotropic magnetic field effect (9,10,16,17,(19)(20)(21)(22)(23)(24)(25)(26)(27). Very little attention has been devoted to the matter we address here: the precision of the compass bearing available from a radical pair sensor (28).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It seems plausible that the optimum performance would require negligible loss of coherence during the lifetime of the radical pair. There have been several theoretical treatments of spin relaxation in the context of magnetoreception, almost all of which have dealt with generic relaxation mechanisms furnished with phenomenological rate constants [36][37][38][39][40][41]. Intriguingly, a few of these studies have indicated that the compass sensitivity could be enhanced by the inclusion of certain abstract spin relaxation pathways [37,38,40,42,43].…”
Section: Introductionmentioning
confidence: 99%